Pengetahuan masyarakat dan pemanfaatan tanaman obat keluarga di desa toya aikmel utara - Muhlisun Azim; Arief Rafsanjani; Tripuspita Yuliana; Puspawan Hariadi (Indonesian Institute For Counseling, Education and Therapy, 2021)
Family Medicinal Plants (TOGA) is an alternative in achieving GERMAS (Healthy Living Community Movement) as an effort to achieve traditional independent health. The success of the use of TOGA is strongly influenced by the level of public knowledge about the benefits of the type of medicinal plants which has been empirically investigated. The data obtained is qualitative data with descriptive approach analysis method. Data collection was carried out by conducting observations, interviews and technical training to the community in an effort to provide knowledge about TOGA and the creation of a TOGA demonstration plot. The results obtained from this activity are the emergence of public awareness of the use of home yard land for the manufacture of living pharmacies as an effort to achieve independent health and the emergence of public interest in the use of TOGA as a UMKM product in the form of packaged drink sachets as a pilot. The importance of public knowledge about TOGA is needed in supporting the success of achieving independent health and efforts to utilize local biological resources in initiating the manufacture of herbal plant-based UMKM products.